2003
DOI: 10.1063/1.1581978
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low threshold-current-density InGaAs quantum-well lasers with emission wavelength of 1215–1233 nm

Abstract: Extremely low threshold-current-density In 0.4 Ga 0.6 As quantum-well ͑QW͒ lasers have been realized in the 1215-1233 nm wavelength regime. The measured room-temperature threshold current density of the InGaAs QW lasers with a cavity length of 1000 m is only 90 A/cm 2 at an emission wavelength of 1233 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…On the other hand, the growth of AlGaAs layers at such low temperatures results in an increased oxygen incorporation and point defect formation, which results in a degradation of the performance of laser diodes [2,3]. Thus, highly strained QWs typically are grown at lower temperatures than the surrounding (Al)GaAs waveguide and cladding layers [4,5]. Several authors have shown, that a post-growth annealing of InGaAs QWs results in a blue shift of the emission wavelength [6,7].…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, the growth of AlGaAs layers at such low temperatures results in an increased oxygen incorporation and point defect formation, which results in a degradation of the performance of laser diodes [2,3]. Thus, highly strained QWs typically are grown at lower temperatures than the surrounding (Al)GaAs waveguide and cladding layers [4,5]. Several authors have shown, that a post-growth annealing of InGaAs QWs results in a blue shift of the emission wavelength [6,7].…”
Section: Introductionmentioning
confidence: 96%
“…11,12 The mixed AsN-based alloys had been studied in the dilute-nitrogen regime specifically for resulting in some of the breakthroughs in the long wavelength lasers on GaAs. [13][14][15][16][17][18] The findings of dilute-nitride GaAs-based alloy had led into the state-of-the-art and low threshold laser devices for the telecommunication applications.…”
Section: Introductionmentioning
confidence: 99%
“…Ryu et al [2] and Salomonsson et al [3] have reported the development of vertical cavity surface emitting lasers (VCSELs) operating around 1220 nm. The longest wavelength of an edge-emitting laser using InGaAs/GaAs QWs is currently at 1233 µm [4]. We have recently reported the development of high-power laser diodes operating at 1206 nm by using InGaAs QWs [5,6].…”
Section: Introductionmentioning
confidence: 99%